Self-Localizing On-Demand Portable Wireless Beacons for Coverage Enhancement of RF Beacon-Based Indoor Localization Systems - Changwei Chen; Solmaz S. Kia (IEEE Journal of Indoor and Seamless Positioning and Navigation)
Localization using relative ranging from radio frequency (RF) wireless beacons installed in an indoor infrastructure is becoming the hallmark of indoor localization systems for asset tracking. However, the coverage of these beacons is not always complete. Moreover, installing the beacons in underutilized spaces is not cost-effective. Deploying portable on-demand beacons to extend the coverage is a cost-effective solution for a robust and reliable RF beacon-based localization system. The challenge though is how to localize these deployed beacons. This article presents a decentralized algorithm to allow deployed beacons to self-localize themselves. This solution removes the rigid requirement of the beacon connectivity, and thus, the need to deploy the beacons in a priori known and surveyed locations. The deployed beacons localize themselves in a collaborative and decentralized manner without the necessity of each of them being connected to three preinstalled infrastructure beacons. The proposed solution is a robust deployment method in the sense that if a portable beacon is moved for any reason, it can automatically relocalize itself in the decentralized manner. Simulation studies of the ultrawideband beacon deployment and localization demonstrates the effectiveness and robustness of the proposed solution in terms of the accurate autonomous position estimation for multiple beacons with $1\text{-m}$ positioning accuracy, and an average error reduction being 79.21% and 34.41% with respect to the conventional methods in literature.